A Low-Power and High-Throughput implementation of the SHA-1 hash function - Michail, Harris; Goutis, Costas E.; Koufopavlou, Odysseas; Kakarountas, Athanasios P. (My University, 2005)
The main applications of the hash functions are met in the fields of communication integrity and signature authentication. A hash function is utilized in the security layer of every communication protocol. However, as protocols evolve and new high-performance applications appear, the throughput of most hash functions seems to reach to a limit. Furthermore, due to the tendency of the market to minimize devices' size and increase their autonomy to make them portable, power issues have also to be considered. The existing SHA-1 Hash Function implementations (SHA-1 is common in many protocols e.g. IPSec) limit throughput to a maximum of 2 Gbps. In this paper, a new implementation comes to exceed this limit improving the throughput by 53%. Furthermore, power dissipation is kept low compared to previous works. © 2005 IEEE.
Keywords: Communication integrity; Hash Functions; Communication protocols